River Quality Analysis and Integration of Community Participation in the Development of the PROKASIH Program - Evianovita, Dwi Intan Nur; Setyono, Prabang; Gravitiani, Evi; Candraningtyas, Callista Fabiola (Universitas Diponegoro, 2026)
River water pollution from domestic and industrial waste remains a major challenge in Indonesia’s environmental governance. The Clean River Program (PROKASIH) was established as a national initiative to control water pollution through collaboration among government agencies, industries, and local communities. However, local implementation often faces constraints, particularly limited community participation and insufficient integration of environmentally friendly infrastructure. This study evaluates the implementation of the Clean River Program in Sukoharjo Regency, examines community participation, identifies influencing factors, and develops an improvement strategy based on social cohesion and sustainable technology. A mixed-methods approach was applied, combining river water quality analysis, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, total suspended solids, nitrate, and phosphate, with a survey of 100 respondents and in-depth interviews. Reliability testing produced a Cronbach’s alpha value of 0.86, while Spearman ’scorrelation analysis showed a significant relationship between education level and participation. The results indicate a program success rate of 58.7%, with community participation classified as moderate. This study proposes the Green–Community River Management (G-CRM) framework, integrating participatory governance and eco-friendly infrastructure to strengthen PROKASIH implementation in line with the 2023–2030 KLHK Clean River Program Roadmap and support Sustainable Development Goal 6.3.